Experiences of women managers in male-dominated working environments - Nyetanyane, Mpho Prudence (Bloemfontein: Central University of Technology, Free State, 2016)
The promotion and advancement of women in male-dominated environments is a topic and concept that has raised many questions, expectations, public interest, and hope. Even though much has been done to open or create platforms for women to enter and advance in male-dominated environments, there are concerns regarding effective implementation of promotion of women. This study focused on the experiences of women managers in male-dominated working environments in a district in South Africa. A feminist study using a qualitative methodology was conducted, and data was gathered through the use of one-on-one personal interviews with women managers who work in male-dominated environments. The women managers that participated in the study revealed that they are still experiencing social and organisational constraints in a country that recently celebrated 21 years of democracy. The findings of the study confirmed that gender inequalities still exist within male-dominated working environments, and this lends substance to the need for a more active and genuine commitment to gender equality and transformation.
Published Thesis
Keywords: Male-dominated working environment; gender stereotyping; feminism; women participation; social identity